Development of E-Books Assisted by Augmented Reality on Respiratory System Material for Grade V Elementary School - Salwa Hanan Andini; Novi Setyasto (Postgraduate, University of Mataram, 2025)
Learning (IPAS) in elementary schools has many obstacles and shortcomings. This study is an R&D study referring to the Borg and Gall model with the aim of testing the feasibility, practicality, and effectiveness of e-book media assisted by augmented reality (AR). Data collection was carried out using test techniques (pretest and posttest) and non-tests in the form of observations, interviews, surveys, and document data. Feasibility is shown from the results of the validation test by expert validators in language, materials, and media showing that the AR-assisted e-book media has met the criteria that are very feasible. Based on the results of the pretest and posttest, it shows that the AR-assisted e-book media is effective in improving student understanding with an increase in the average pretest and posttest scores shown from the T-test results showing a value of 0.001, and the N-gain test results obtained 0.85. Practicality is shown from the results of the teacher and student response questionnaire which received very positive responses from teachers and students. The data shows that AR-assisted e-book media is practical, feasible, and effective in improving understanding of the human respiratory system material in class V of SD Negeri Karangjati 04.